Upaya Penanganan Korban Kekerasan Seksual di Dinas Sosial Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Pesisir Selatan - Mayora, Elsa; Masrial; Wusqo, Urwatul (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2023)
The number of victims of sexual violence in the Social Service of Women's Empowerment and Child Protection of Pesisir Selatan Regency is increasing. Victims experience depression, anxiety about the future, shame, low self-esteem and social withdrawal. It is in such conditions that victims of sexual violence need attention and protection. The purpose of this research is to: find out the programs, materials, and methods of guidance in handling victims of sexual violence at the Social Service of Women's Empowerment and Child Protection of Pesisir Selatan Regency. This research is a field research (field research) using qualitative methods that are descriptive in nature. Determination of research subjects was carried out by purposive sampling obtained 6 people. The results showed that: First, the guidance program in handling victims of sexual violence, namely: child protection programs through strengthening and services provided by institutions and women's protection programs through case facility services and mentoring. Second, the guidance or socialization material for handling victims of sexual violence with material to stop violence against women and children, as well as the role of the police. Third, the method of guidance in handling victims of sexual violence is through direct complaints. How to provide assistance to victims by assessing the needs of victims, recommending referral services (health services, psychological services and social rehabilitation, legal aid services) and repatriation.